Pesantren and the Economic Development in the Perspective of Maqashid Al-Shari’ah - Jazil, Saiful; Fahmi, Muhammad; Prasetia, Senata Adi; Faizin, Moh.; Sholihuddin, Muh. (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2021)
Modernization to deliver the process in diversifying the socio-economic role of pesantren is undeniable things. Consequently, pesantren must take immediate action if they want to maintain their role and function. In this context, this article wants to describe the widespread mandate of a pesantren in Jember, namely Pesantren Nurul Qornain (PNQ), those takes part –not only empowerment in the field of education- but also play role in the development of economic enterprises. This is then reviewed in the perspective of maqashid al-shari’ah (the purpose of shari’a). Throughout qualitative study, this article explains that pesantren alumni and local society involved in the management of PNQ economic enterprises. Some of developed business unit in the area of agriculture, trading, animal farm, plantation, and mining. Furthermore, the main factor behind PNQ in managing economic enterprises is pesantren sovereignty. It is initiated by kiai (the leader of pesantren). According to him, pesantren can develop rapidly if they sovereign in all aspects. This sovereignty is interpreted as economic sovereignty. However, economic development is as determining factor in supporting the existence of pesantren. Additionally, the development of economic enterprises carries out by PNQ in line with the value of hifdhul maal (the maintenance of property). Hence, it is prospective benefits if it can be replicated by Islamic educational institution nowadays.